A Monitoring System for Transboundary Foot and Mouth Disease (FMD) considering the Demographic Characteristics in Gairo, Tanzania - Kijazi, A.; Kisangiri, M.; Kaijage, S.; Shirima, G. (Engineering, Technology & Applied Science Research, 2021)
Foot and Mouth Disease (FMD) is present in many countries, including Tanzania. Gairo is among the districts that frequently face FMD. This study found that the current mechanism for communicating FMD in Gairo district suffers from a long chain of information flow that causes delay and insufficient information for FMD control. Therefore, this study aimed to explore the implementation of an information system named "Monitoring System for Transboundary Foot and Mouth Disease," developed purposely to provide a standard platform for communicating FMD between livestock keepers and other stakeholders in the district. The system enables timely sharing of FMD events such as outbreaks, precaution measures, clinical signs, and negative impacts using Short Message Services (SMS), Unstructured Supplementary Service Data (USSD), and Voice Calls (robo-calls) through the mobile phones. Also, livestock keepers may report FMD outbreaks direct to the system using feature phones. The Statistical Package for Social Sciences (SPSS) was used to analyze data and Microsoft Visio was used for drawing the system architecture and information flow diagram. Finally, the system was implemented using PHP hypertext processor, JQuery, HTML, JSON, JavaScript, MySQL, and Apache webserver.